2010
DOI: 10.1515/ijnsns.2010.11.9.725
|View full text |Cite
|
Sign up to set email alerts
|

New Exact and Explicit Travelling Wave Solutions for the Coupled Higgs Equation and a Nonlinear Variant of the PHI-four Equation

Abstract: An analytic study on a complex nonlinear system (Coupled Higgs equation) and a nonlinear variant of the PHI-four equation is presented in this paper. The Exp-function method is employed to derive exact periodic and generalized solitary solutions of these equations. The solutions are compared with those obtained by the tanh method, the sine-cosine method and the Weierstrass elliptic function method, furthermore, new and more general solutions are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…We can say that the traveling wave solutions obtained in this study are different and more general than the traveling wave solutions obtained by Khajeh et al, 38 which we discussed in the introduction. This situation constitutes one of the original values of our study.…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations
“…We can say that the traveling wave solutions obtained in this study are different and more general than the traveling wave solutions obtained by Khajeh et al, 38 which we discussed in the introduction. This situation constitutes one of the original values of our study.…”
Section: Resultscontrasting
confidence: 69%
“…These solutions are more general than traveling wave solutions and differ from the literature. 38 It was observed that the solutions obtained to test the reliability of the MGERFM provided the CHS after symbolic calculations. In addition, in the results and discussion section, the behaviors exhibited by the traveling wave for different values of the soliton frequency and wave number in Equation (3.8) have been presented as a simulation in Figure 10, and the physical interpretations of parameters have been discussed in detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conditions to guarantee the existence of these solutions were also summarized in the same study. Various solutions in hyperbolic or trigonometric function forms were determined by implementation of exponential function technique [6]. Jacobi type periodic, hyperbolic and trigonometric solutions in wave forms were set by an algebraic method [7].…”
Section: Introductionmentioning
confidence: 99%